PENGELOLAAN DAYA TARIK WISATA DAN PELESTARIAN BUDAYA MASYARAKAT OSING DI DESA KEMIREN, BANYUWANGI JAWA TIMUR - Putu Herny Susanti; I Gede Agus Deny Permana; Ni Made Ayuning Pramesti; I Made Purnawan Dharma P; Devi Triana Puspa; Ni Kadek Dwinda Sri Rahayu; Abiradama Sudayasa; Ida Bagus Nyoman Weda; Dewa Made Sastra Wiatmika (Bajang Institute, 2025)
Kemiren Village in Banyuwangi is a cultural enclave of the Osing community, rich in local traditions and identity. This research aims to analyze the dynamics of Osing cultural preservation amidst modernization and globalization, identify preservation strategies implemented by the community, and analyze the role of stakeholders in managing Kemiren Village as a cultural tourism village. Using a descriptive qualitative approach with a case study, data were collected through participatory observation, in-depth interviews, and documentation studies. SWOT analysis to formulate cultural preservation strategies. The findings indicate that Kemiren Village is in the development stage of its tourism area life cycle, with authentic Osing culture as its main attraction. Preservation strategies are collaborative and community-based, involving local communities, traditional institutions, government, academics, and the private sector. The role of traditional institution and Pokdarwis is central in the planning and implementation of cultural activities as well as in providing tourism services. Key challenges include the absence of formal regulations (Perdes), transportation accessibility, disparities in homestay quality, and the potential for cultural commercialization. Recommendations include drafting local regulations, enhancing local human resource capacity, diversifying educational tourism products, and strengthening sustainability monitoring systems. This research contributes to the study of local cultural preservation and community-based tourism destination management